Electrocatalysis of the Oxygen Reduction Reaction and the Formic Acid Oxidation Reaction on BN/Pd Composites Prepared Sonochemically. Issue 12 (1st January 2017) - Zuo, Ling-Xia; Jiang, Li-Ping
Abstract : Highly active and inexpensive electrocatalysts are critical for metal-O2 batteries or fuel cells. In the present study, we synthesized single boron nitride nanosheet-supported palladium (BN/Pd) composites via a simple sonochemical method. The properties of the synthesized products were studied by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), SEM energy-dispersive X-ray spectroscopy (SEM-EDX), transmission electron microscopy (TEM) and high-resolution TEM (HRTEM). The as-prepared BN/Pd composites showed favorable kinetics (four-electron transfer), high activity and excellent durability for the oxygen reduction reaction (ORR) in alkaline media. The catalyst also exhibited strong electrocatalytic activity and excellent long-term durability for formic acid oxidation (FAO) in acidic media. Notably, compared with the commercial Pt/C catalyst, the synthesized catalyst exhibited superior performance toward FAO in acidic media. Therefore, we expect this catalyst to be a better substitute for the commercial Pt/C catalyst, with an enhanced and durable performance as an anode and cathode material for direct formic acid fuel cells (DFAFCs). Moreover, the sonochemical method employed here can be easily extended to prepare other composite-based electrocatalysts for fuel cell applications. Our work demonstrates the wide potential of BN/Pd composites for promising applications.